KESIAPAN GURU DALAM MENGHADAPI PENDIDIKAN INKLUSI UNTUK ANAK BERKEBUTUHAN KHUSUS - Afifa Tsabita Muttaqya; Aisyah Sabrina Priyanto; Anggi Nur Hidayah; Septi Fitri Meilana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education is an approach that prioritizes providing a supportive learning environment for all students, including ABK. This research uses a qualitative approach with a case study method. An in-depth interview was conducted with a grade 1 teacher at SDN Susukan 09 Pagi to identify the teacher's understanding, challenges and strategies in teaching ABK. Teacher readiness is a key factor in the successful implementation of inclusive education, including pedagogical competence, understanding the needs of ABK, inclusive attitudes, and adequate facility support. The results of the study show that the majority of teachers still face challenges in understanding the characteristics and needs of ABK, limited special training, and a lack of resource support. However, a positive attitude towards inclusive education is an important asset for increasing their competence. With ongoing training, mentoring and strengthening school policies, it is hoped that teacher readiness can increase significantly so that inclusive education can run effectively and inclusively for all children.